Molecular Assessment of Kappaphycus alvarezii Cultivated in Tarakan based on cox2-3 Spacer - Gloria Ika Satriani; Dinar Tri Soelistyowati; Alimuddin Alimuddin; Harton Arfah; Irzal Effendi (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2023)
The seaweed Kappaphycus alvarezii is a leading aquaculture commodity possessing high economic value that has been used as a raw material for various natural products, food, and pharmaceutical industries. The main challenge regarding its production, especially in Tarakan, is the supply of superior seeds. Therefore, this study aims to obtain phylogenetic information and the cultivation performance of the selected seeds by identifying genetic sources based on molecular markers. DNA sequencing was analyzed using the molecular marker cyclooxygenase 2-3 intergenic spacer (cox2-3 spacer) on the 16 cultivars collection from around Indonesia. Four haplotypes representing the K. alvarezii variant to be cultivated in Tarakan City were produced based on the phylogenetic clustering and further molecular analysis using a cox2-3 spacer mitochondrial DNA marker. These include the Kupang and Natuna varieties, also referred to as Lampung seedlings, which is a tissue culture plantlets used for development at SEAMEO-BIOTROP Bogor and propagated by the Lampung Marine Aquaculture Center (BBPBL), Tarakan. These varieties have genetic distances (pairwise comparisons based on the mean Kimura 2-parameter model) ranging from 0.000-0.243 units. The cultivation was carried out for 30 days in the waters of Tanjung Batu (Tj. Batu) Mamburungan, Tarakan, North Kalimantan. The result showed that the Lampung cultivar (Natuna) has a superior daily growth rate (DGR) and carrageenan yield compared to the local cultivars (Mamburungan Tanjung Batu (Takalar), Tarakan, and Kupang). Furthermore, the genetic analysis with cox2-3 spacer markers could be an effective seed selection tool for tracing genetic information in developing superior seedlings in aquaculture activities.